A longitudinal study on the relationships between maternal parenting style, children’s victimization, and self-esteem - Cheng, Dandan; Wang, Cui; Xiong, Minghui; Mo, Ran; Nie, Yuxuan; Liu, Junsheng (Frontiers in Psychiatry, 2025)
BackgroundPrevious studies have established that parenting style and self-esteem affect children’s risk of victimization. This study further investigates the longitudinal mechanisms by which maternal warmth and rejection, along with self-esteem, influence children’s likelihood of victimization.MethodThis study used a longitudinal design to examine the relationships between two key dimensions of maternal parenting styles (warmth and rejection), victimization, and self-esteem during middle and late childhood. It involved 607 third- and fourth-grade students and their mothers. A multi-informant approach assessed children’s victimization, self-esteem, and mothers’ parenting styles across three assessments over three years (T1, T2, and T3).ResultsSelf-esteem and maternal rejection negatively predicted each other, as did self-esteem and victimization at corresponding time points. By contrast, maternal warmth positively predicted self-esteem, and victimization was positively associated with maternal rejection. Additionally, victimization negatively predicted maternal warmth. The developmental cascade analysis demonstrated that self-esteem at T2 mediated the relationship between victimization at T1 and maternal rejection at T3. Similarly, self-esteem at T2 also mediated the relationship between maternal warmth at T1 and victimization at T3.ConclusionsThese findings confirm the significant role of maternal parenting styles in fostering children’s self-esteem and reducing victimization, highlighting the dynamic interactions among key variables.